Protective Effect of Croton macrostachyus (Euphorbiaceae) Stem Bark on Cyclophosphamide-Induced Nephrotoxicity in Rats - Ayza MA; Rajkapoor B; Wondafrash DZ; Berhe AH (Dove Medical Press, 2020)
Muluken Altaye Ayza,1 Balasubramanian Rajkapoor,1,2 Dawit Zewdu Wondafrash,1 Abera Hadgu Berhe1 1Department of Pharmacology and Toxicology, School of Pharmacy, College of Health Sciences, Mekelle University, Mekelle, Ethiopia; 2Department of Pharmacology, JKK Nattraja College of Pharmacy, Komarapalayam 638 183, Tamilnadu, IndiaCorrespondence: Muluken Altaye Ayza Tel +251-916707913Email Mulealto1@gmail.comBackground: Cyclophosphamide is an alkylating antineoplastic agent and its major limitation is injury to normal tissue, leading to multiple organ toxicity, including kidney, heart, liver and reproductive toxicity. Croton macrostachyus (Euphorbiaceae) has been used in Ethiopian traditional medicine to manage renal diseases.Objective: The present study aims to assess the protective effect of the stem bark extract and solvent fractions of Croton macrostachyus on cyclophosphamide-induced nephrotoxicity in rats.Methods: Nephrotoxicity was induced using cyclophosphamide 200 mg/kg i.p injection on the first day of the experiment. The negative control groups were administered with cyclophosphamide alone (200 mg/kg, i.p.). The crude extracts were administered at three dose levels (100, 200, and 400 mg/kg), while aqueous and ethyl acetate fractions were given at two dose levels (100 and 200 mg/kg). Excepting the normal control, all groups were subjected to cyclophosphamide toxicity on the first day.Results: Treatment with crude extract 100 mg/kg and ethyl acetate fraction significantly decreased kidney-to-body weight ratio (P < 0.001). In addition, treatment with Croton macrostachyus crude extract and solvent fractions significantly decreased serum blood urea nitrogen (BUN) level (P < 0.001). Treatment with 100 and 200 mg/kg of ethyl acetate fraction significantly decreased serum creatinine level. Histopathological results confirmed the protective effect of the crude extract and solvent fractions of Croton macrostachyus.Conclusion: Croton macrostachyus possesses nephroprotective activities and it could be a possible source of treatment for cyclophosphamide-induced nephrotoxicity.Keywords: Croton macrostachyus, cyclophosphamide, nephrotoxicity, creatinine, blood urea nitrogen